2013
DOI: 10.1002/jcph.151
|View full text |Cite
|
Sign up to set email alerts
|

Co‐medication of pravastatin and paroxetine—A categorical study

Abstract: Electronic Medical Records (EMRs) are wealthy storehouses of patient information, to which data mining techniques can be prudently applied to reveal clinically significant patterns. Detecting patterns in drug-drug interactions, leading to adverse drug reactions is a powerful application of EMR data mining. Adverse effects of drug treatments can be investigated by mining clinical laboratory tests data which are reliable indicators of abnormal physiological functions. We report here the co-medication effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The main finding of this study was that although paroxetine itself produced a trend toward impaired glycemic control and insulin secretion in diabetic rats, comedication with paroxetine and pravastatin further deteriorated glucose homeostasis, which was in accordance with clinical reports [14][15][16] . Compared with the DM rats, the DM-CO rats displayed lower insulin levels in both the serum and pancreas, which was in line with a decrease in the expression of pancreatic Insulin-2 mRNA, inferring that insulin biosynthesis was inhibited.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main finding of this study was that although paroxetine itself produced a trend toward impaired glycemic control and insulin secretion in diabetic rats, comedication with paroxetine and pravastatin further deteriorated glucose homeostasis, which was in accordance with clinical reports [14][15][16] . Compared with the DM rats, the DM-CO rats displayed lower insulin levels in both the serum and pancreas, which was in line with a decrease in the expression of pancreatic Insulin-2 mRNA, inferring that insulin biosynthesis was inhibited.…”
Section: Discussionsupporting
confidence: 90%
“…However, multiple reports have demonstrated that comedication with pravastatin and paroxetine can increase the risk of elevated blood glucose levels in diabetic patients [14][15][16] , although neither pravastatin nor paroxetine alone have shown an effect on glucose levels. The real mechanism leading to the adverse drug reaction Paroxetine is metabolized in the liver mainly by CYP2D6 [17] .…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports, based on a retrospective analysis of electronic medical records, have demonstrated that comedication with paroxetine and pravastatin can increase the risk of elevated blood glucose levels in diabetic patients, although neither paroxetine nor pravastatin alone has shown an effect on glucose levels . The synergistic effect on blood glucose was limited to paroxetine and pravastatin and was not a class action between SSRIs and statins.…”
Section: Resultsmentioning
confidence: 99%
“…Possible explanations include the limited number of patients and the very low affinity towards M 3 muscarinic receptors of paroxetine compared with other AD_antaM 3 (amitriptyline had the highest affinity) [25]. Increasing exposure to paroxetine (i.e., by combining with pravastatin) has been shown to increase the risk for T2DM [2628]. However, we could not examine the paroxetine–pravastatin combination because it was used by only three cases.…”
Section: Discussionmentioning
confidence: 99%